Current trends in the evolution of administrative and legal regulation - Nikishkin A. V., Vetrova E. V., Stepanov I. V. (Law, Economics and Management, 2020)
This article presents the essence of the current trend in the evolution of administrative regulation. The assessment of identifying current problematic trends in the evolution of administrative and legal regulation is given
Keywords: административное право; административно-правовое регулирование; проблемные тенденции; административная юстиция; современные тенденции; administrative law; administrative and legal regulation; problematic trends; administrative justice; current trends